PUISI PERLAWANAN SEBAGAI KRITIK SOSIAL DALAM KUMPULAN POSTINGAN AKUN INSTAGRAM OKKY MADASARI: SOSIOLOGI MARXISME - Ridwan, Ridwan; Diana, Ririn Sefty (Cakrawala Indonesia, 2025)
Research on Resistance Poetry as Marxist Social Criticism in Okky Madasari's Collection of Poetry Posts aims to describe Okky Madasari's poetry on the Instagram platform, using Karl Marx's marxism approach as the basis for analysis and examining social criticism in the poems. The method used is descriptive qualitative with data sources of poems that represent social inequality and class struggle. The results show that Okky Madasari's poems contain five components of Marxism: political economy criticism, class struggle theory, social structure, and upper and lower class relations. The poems consistently highlight the exploitation of inequality, and resistance to the regime, becoming a form of symbolic resistance in the Indonesian context